Maturidade em gerenciamento de projetos e orientação empreendedora: análise das relações em organizações de software - Carneiro, Karoline Doro Alves (2012)
This study proposes to verify the existence of relationship between project management maturity and entrepreneurial orientation in a context of software organizations. In this way, the literature related to project management maturity and entrepreneurial orientation has been addressed. Based on a review of theoretical and conceptual approach constructs, it was possible to propose a theoretical model which suggests that the entrepreneurial orientation of software organizations has positive relationship with their project management maturity. The Structural Equation Modeling was applied to evaluate the model, using the estimation method PLS (Partial Least Square). The sample consists of 140 cases, mainly by software organizations associated with ABES (Associação Brasileira de Empresas de Software). The descriptive analysis of the constructs indicates average scores for project management maturity and entrepreneurial orientation in the participating companies. The model was validated and the study hypothesis was confirmed. The result of the study suggests that the entrepreneurial orientation influences project management maturity in the software organizations investigated. As contributions, the results may collaborate with the theoretical discussions of project management maturity and entrepreneurial orientation. It also provides support for decision making and software organizations management. Furthermore, this study can motivate other empirical studies in different organizational contexts.